An Exploratory Overview of Agriculture Finance in Indonesia - World Bank (World Bank, Washington, DC, 2020)
The Government of Indonesia is aiming to diversify the country’s food system by developing and strengthening high-value-added and more nutrient-rich value chains. In this regard, the government is focusing on diversifying into horticulture and small ruminant livestock. Undertaking Value Chain Analysis (VCA) is a critical part of this process as it helps in the identification of constraints and opportunities in relevant sectors. Agriculture funding and finance are vital components of this analytical process. This report presents a preliminary overview of opportunities and constraints as well as areas for future interventions. The analysis is based on a World Bank and FAO scoping mission to Indonesia that took place between March 2 - March 13, 2020. This report focuses on the supply-side of capital. The key findings suggest that supply-side constraints are minimal. The liquidity in Indonesia’s banking system is enough and there already exist extensive physical banking networks within the country. The Indonesian banking networks include a selection of commercial and specialized banks, membership-based groups, and fintech organizations. Also, there exist several large food manufacturers that could potentially aid in the process of financing and the creation of linkages through vertical integration of value chains. The Small and Medium Size Enterprises (SMEs) in the food and agriculture sectors have been growing strongly, and they can act as accelerators and facilitate the process. The Indonesian government is supporting the development of value chains and has been actively promoting the creation of farmer organizations to aid the process. Lastly, there exists a demand for the creation of a blended finance facility that could help amplify the effects of the value chain projects, and the Tropical Landscapes Finance Facility (TLFF) is a proof of such a concept that is working well in Indonesia.